PENGUKURAN OVITRAP INDEX (OI) SEBAGAI GAMBARAN KEPADATAN NYAMUK DI RW 6 KELURAHAN TENGGILIS MEJOYO KECAMATAN TENGGILIS MEJOYO KOTA SURABAYA - Edza Aria Wikurendra (Universitas Fort De Kock, 2020)
Environment that is far from dirty elements and disturbing animals is one of the criteria for a clean and healthy environment. The potential for Dengue Hemorrhagic Fever (DHF) transmission can be illustrated by the density of mosquito populations in an area. Ovitrap index (OI) is one method that can be used to measure mosquito populations. Researchers are interested in conducting research on the measurement of mosquito density with the Ovitrap Index and the tendency to lay eggs at Aedes spp. inside or outside the house. The purpose of this study was to determine the density of mosquitoes with Ovitrap Index (OI) in RW 6, Tenggilis Mejoyo Sub-District, Tenggilis Mejoyo Sub-District, Surabaya City. This research is a descriptive study with cross sectional approach. The research sample is the larvae of the Aedes spp. who was trapped in an ovitrap in RW 6, Tenggilis Mejoyo Sub-District, Tenggilis Mejoyo Sub-District, Surabaya City. Installation of ovitrap in the house found positive ovitrap contained mosquito eggs in almost all RT. Installation of ovitrap outside the home found positive ovitrap contained mosquito eggs only at RT 01 and RT 02 at week IV. The mosquito larvae examined were Aedes Aegypti and Aedes Albopictus species spread in all RT. Suggestions for further research are to increase the number of samples and ovitraps that are added so that the results become more varied.